The current situation and associated factors of the psychological capital of nurses’ second victims in China: a cross-sectional study - Zhuoqing Deng; Qianfei Li; Hongyan Zan; Xiaohong Zhang; Ya‘nan Zhang; Zhiheng Gao (BMC Nursing)
Abstract Background The level of psychological capital of nurses’ second victims is critical to alleviate their negative experience after a safety incident. The purpose of this study is to understand the current status of psychological capital and associated factors of nurses after experiencing patient safety incidents. Methods In May 2024, an online survey was conducted on nurses from 2 tertiary hospitals and 2 secondary hospitals in Shanxi Province who had experienced patient safety incidents in the past year using the General Information Questionnaire, the Patient Safety Incident Characteristics Questionnaire, and the Nurses’ Psychological Capital Questionnaire, and finally 456 nurses filled out the questionnaire. Results A total of 423 valid questionnaires were collected, and the recovery rate of valid questionnaires was 92.76%. The total score of psychological capital of the nurses’ second victims was (89.13 ± 14.86), and the results of multiple linear regression showed that hospital level, department, the type of patient safety incident, the level of patient safety incident, and whether or not they were supported were independent associated factors of the psychological capital of the second victims (P < 0.05), which could explain 21.00% of the total variation. Conclusion The psychological capital of the nurses’ second victims was at a medium level. At the hospital level, the focus should be on nurses in tertiary hospitals. At the department level, the focus should be on the nurses in the oncology department. From the level of patient safety incidents, we should focus on the nurses with high event level and drug administration errors, and provide timely intervention support after the incident, so as to improve the psychological capital level of the second victims. Clinical trial number Not applicable.